Sensory, Phytochemical, and Antioxidant Evaluation of Dark Chocolate Fortified with Spent Coffee Grounds - Jona Anne Elaine Maningas; Karen A. Manaig; Alberto D. Yazon (Inclusive Society and Sustainability Studies, 2026)
This study experimentally evaluated the sensory acceptability, total phenolic content, and antioxidant capacity of dark chocolate fortified with Spent Coffee Grounds (SCG) within a sustainability-oriented food innovation framework. Three formulations containing 15 g, 25 g, and 50 g SCG were assessed by 60 evaluators using a 9-point Hedonic Scale. One-way ANOVA and Tukey’s HSD determined significant differences among samples (p < 0.05). Results revealed that the formulation containing 50 g SCG achieved significantly higher overall acceptability, indicating that increased SCG incorporation did not compromise sensory quality. The selected formulation exhibited higher total phenolic content and strong DPPH radical-scavenging activity, confirming functional improvement. This study’s novelty lies in integrating sensory evaluation, phytochemical quantification, and antioxidant analysis across multiple formulations to identify an optimal balance between consumer acceptability and functional enhancement within a waste-valorization framework. Findings extend functional food theory by demonstrating that high-level incorporation of SCG can enhance bioactivity without reducing consumer acceptance when applied within a compatible cocoa-based matrix. The study contributes to sustainable food systems by providing an evidence-based model for transforming agro-industrial waste into value-added functional products.